Character Education Within A Policy Framework: Bridging Conceptual Definitions and School Practices - Muhammad Zein; Rival Rival; Bahtiar Bahtiar; Santi Muhammadun; Isbat Talib (Electronic Journal of Education, Social Economics and Technology, 2025)
Character education is one of the strategic agendas in national education policy aimed at shaping students who are faithful, have noble character, and possess a complete personality amidst the challenges of globalization and digital transformation. The development of digital technology has brought significant changes to students' learning patterns and behavior, which on one hand opens up opportunities for competence development, but on the other hand raises ethical challenges and value degradation. This article aims to analyze character education within the framework of educational policy, focusing on the connection between concepts, policies, and implementation practices in schools during the digital era. This research uses a qualitative approach with a literature study design and educational policy analysis enriched by the results of initial observations in the school environment. Data were obtained from national education policy documents, scientific literature, and previous research findings, and then analyzed using content analysis techniques. The research findings indicate that, conceptually and normatively, character education policies have been formulated comprehensively and are relevant to the challenges of the digital era. However, its implementation at the educational unit level still faces various obstacles, particularly in integrating character values into technology-based learning. This research emphasizes the importance of strengthening character education implementation strategies to align with the dynamics of digital education.